Carbon monoxide sensing properties of B-, Al- and Ga-doped Si nanowires. (22nd March 2018) - de Santiago, F; Trejo, A; Miranda, A; Salazar, F; Carvajal, E; Pérez, L A; Cruz-Irisson, M
Abstract: Silicon nanowires (SiNWs) are considered as potential chemical sensors due to their large surface-to-volume ratio and their possible integration into arrays for nanotechnological applications. Detection of harmful gases like CO has been experimentally demonstrated, however, the influence of doping on the sensing capacity of SiNWs has not yet been reported. For this work, we theoretically studied the surface adsorption of a CO molecule on hydrogen-passivated SiNWs grown along the [111] crystallographic direction and compared it with the adsorption of other molecules such as NO, and O2 . Three nanowire diameters and three dopant elements (B, Al and Ga) were considered, and calculations were done within the density functional theory framework. The results indicate that CO molecules are more strongly adsorbed on the doped SiNW than on the pristine SiNW. The following trend was observed for the CO adsorption energies: E A [B-doped] > E A [Al-doped] > E A [Ga-doped] > E A [undoped], for all diameters. The electronic charge transfers between the SiNWs and the adsorbed CO were estimated by using a Voronoi population analysis. The CO adsorbed onto the undoped SiNWs has an electron-acceptor character, while the CO adsorbed onto the B-, Al-, and Ga-doped SiNWs exhibits an electron-donor character. Comparing these results with the ones obtained for the NO and O2 adsorption, the larger CO adsorption energy on B-doped SiNWs indicates their good selectivity towards CO. These results suggest that SiNW-based sensors of toxic gases could represent a clear and advantageous application of nanotechnology in the improvement of human quality of life.